2021
DOI: 10.1039/d1na00610j
|View full text |Cite
|
Sign up to set email alerts
|

Metal–organic framework combined with CaO2 nanoparticles for enhanced and targeted photodynamic therapy

Abstract: Photodynamic therapy (PDT) has been rapidly developing an effective therapeutic approach in clinical. However, hypoxia seriously limits the effectiveness of PDT. Here, we report a porphyrinic based metal-organic framework combined...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…[ 47 ] Furthermore, the UV–vis absorption spectra revealed that PM and PMH were successfully constructed and had a high absorbance at 660 nm, indicating that PMH had greater photodynamic potential (Figure 1F). [ 48 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 47 ] Furthermore, the UV–vis absorption spectra revealed that PM and PMH were successfully constructed and had a high absorbance at 660 nm, indicating that PMH had greater photodynamic potential (Figure 1F). [ 48 ]…”
Section: Resultsmentioning
confidence: 99%
“…[47] Furthermore, the UV-vis absorption spectra revealed that PM and PMH were successfully constructed and had a high absorbance at 660 nm, indicating that PMH had greater photodynamic potential (Figure 1F). [48] The hydrodynamic particle size and zeta potential measured by dynamic laser scattering (DLS) were employed to monitor the preparation process. As shown in Figure 1G, the hydrodynamic particle size of the prepared PCN-224, PM, and PMH successively increased.…”
Section: Preparation and Characterization Of Pcn-224@mn 3 O 4 @Ha (Pmh)mentioning
confidence: 99%
“…aiming to achieve tumor hypoxia relief ( Fig. 2 A) [44] . PCN-224-CaO 2 -HA was obtained by combining porphyrin-based metal-organic cytoskeleton (PCN-224) with hyaluronate (HA)-modified CaO 2 , which generated sufficient O 2 to address the PDT limitation via the reaction between CaO 2 and H 2 O.…”
Section: Oxygen-dependent Pdtmentioning
confidence: 99%
“…(A) The PCN-224-CaO 2— HA NPs were tail vein injected, HA maintained the stability and targeted tumor cells, while CaO 2 reacted with H 2 O to generate O 2 for tumor hypoxia relief. Reproduced from [44] with permission from Royal Society of Chemistry. (B) PCCN accumulated at tumor sites tumor cells and C 3 N 4 participated in water splitting to produce enough O 2 to promote PDT.…”
Section: Oxygen-dependent Pdtmentioning
confidence: 99%
“…To solve the problem, Zhang and coworkers modified calcium oxide nanoparticles on PCN-224 to construct an in situ oxygen production system. 124 The protection of calcium oxide by porphyrin-based MOFs solves the problem of water stability, while calcium oxide produces an endogenous supply of the MOF for PDT. Furthermore, they loaded the MOF with the targeted molecule hyaluronic acid (HA).…”
Section: Targeted Applications Of Porphyrin-based Mofsmentioning
confidence: 99%